“Evaluasi Energi dan Strategi Optimalisasi Kinerja Bangunan Eksisting untuk Mengembangkan Model Desain Bangunan Berkelanjutan Berbasis Aplikasi EDGE: Studi Kasus Gedung FEBI UIN Sunan Kalijaga Yogyakarta.” - Purnaumbara, Kartiansmara L.; Oktava, Arif; Sidik, Muhammad J.; Pratama, Naufal R. (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
This study analyzes the potential of the EDGE (Excellence in Design for Greater Efficiencies) application as an evidence-based design and policy instrument to support the green campus transformation of Indonesia’s Islamic Higher Education Institutions (PTKIN), particularly in anticipation of the future development of the Integrated Campus of UIN Sunan Kalijaga. A qualitative exploratory approach with a simulation-based case study was applied to the Faculty of Islamic Economics and Business (FEBI) Building at UIN Sunan Kalijaga Yogyakarta. Technical building specifications were examined to evaluate existing energy performance and to test design optimization scenarios. The simulation results indicate that the FEBI Building already meets the EDGE energy performance standard, achieving an energy efficiency of 32.42%, while still presenting opportunities for improvement through the integration of passive and active design strategies. Design optimization measures—comprising refined building orientation strategies, controlled fenestration, enhanced façade performance, photovoltaic system integration, and occupancy-based sensor implementation—were shown to increase the building’s energy-efficiency potential to 53.42%. These findings provide the basis for developing an EDGE-based sustainable building design guideline, which can serve as a strategic reference for campus development at UIN Sunan Kalijaga Yogyakarta toward a lower-carbon transformation of PTKIN institutions.